Developing Ethical Competence: Some Considerations Regarding Virtue, Deliberation, Intention, and Guilt. (18th January 2018) - Jacobs, Richard M.
Abstract : This article inquires into what it means for public administrators to intend a good action and then accept responsibility when bad outcomes result. Explicating Anscombe's approach to virtue ethics and deliberation, the intention can be known with certainty and responsibility then be assigned. The concepts of "feeling guilty" and "experiencing guilt" are differentiated, making it possible to envision how public administrators experience guilt for bad outcomes and, by accepting responsibility for them, hone ethical competence (Cooper & Menzel, 2013 ). These experiences also enable public administrators to model for the other members of their organizations how they might hone ethical competence and collaborate in building more ethical public service organizations.